Cele nowoczesnego handlu - Szpaderski, Andrzej (Wydział Prawa i Administracji UAM, 1969)
Conception of modern trade, deriving its acticity from social needs and not from the principle of the businessman's profit, is understood by the author as professional intervention in the exchange of goods done by the help of purchase deeds and bills of sale, which consists in joining and coordinating by means of market methods submitted by tenderers and receivers of goods and which aims at: 1. Optimum conditions of meeting the demands on consumers' goods and producers' goods (in short optimum market conditions); 2. Minimum time of exchange transactions. Optimum condition of meeting the demands means the function of accumulation of optimum supplies of the market. Optimum market condition is the state of supplying with goods that allows the purchaser to obtain not only maximum satisfaction but also the consciousness of full rationalization of the carried expenses. Conception of trade aiming at minimum time of exchange should be understood as organization that simplifies and rationalizes at the processes of exchange. Only such trade ought to be considered modern, because the aim nad sense of the progress of modernity is simplification, rationalization and even acceleration of the whole activity that is useful for the development of consumption.
Aims of Modern Trade